2016
DOI: 10.1107/s2414314616007719
|View full text |Cite
|
Sign up to set email alerts
|

Ethyl 2-(6-bromo-2-phenyl-1H-imidazo[4,5-b]pyridin-1-yl)acetate

Abstract: In the title compound, C16H14BrN3O2, the fused-ring system is essentially planar, with the largest deviation from the mean plane being 0.0216 (15) Å for the substituted N atom of the five-membered ring, the plane of which makes dihedral angles of 28.50 (7) and 77.48 (7)° with the terminal phenyl ring and the ethoxycarbonylmethyl group mean planes, respectively. In the crystal, C—H...N hydrogen bonds link the molecules into inversion dimers. These combine with weak C—H...N contacts to stack the molecules into c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 9 publications
0
1
0
Order By: Relevance
“…For example, they are known for their anticancer activity (Dash et al, 2008) and antibacterial (Capelli et al, 2006), antimitotic (Temple, 1990) and tuberculostatic (Bukowski & Janowiec, 1989) properties. In a previous study, we reported the synthesis of ethyl 2-(6-bromo-2-phenyl-1H-imidazo [4,5-b]-pyridin-1-yl)acetate (Hjouji et al, 2016). The present study is extended to the synthesis of the ethyl 2-(6-bromo-2-phenyl-3H-imidazo [4,5-b]pyridin-3-yl)acetate regioisomer, by the action of ethyl 2-bromoacetate on 6-bromo-2-phenyl-3H-imidazo [4,5-b]pyridine under the same conditions.…”
Section: Structure Descriptionmentioning
confidence: 99%
“…For example, they are known for their anticancer activity (Dash et al, 2008) and antibacterial (Capelli et al, 2006), antimitotic (Temple, 1990) and tuberculostatic (Bukowski & Janowiec, 1989) properties. In a previous study, we reported the synthesis of ethyl 2-(6-bromo-2-phenyl-1H-imidazo [4,5-b]-pyridin-1-yl)acetate (Hjouji et al, 2016). The present study is extended to the synthesis of the ethyl 2-(6-bromo-2-phenyl-3H-imidazo [4,5-b]pyridin-3-yl)acetate regioisomer, by the action of ethyl 2-bromoacetate on 6-bromo-2-phenyl-3H-imidazo [4,5-b]pyridine under the same conditions.…”
Section: Structure Descriptionmentioning
confidence: 99%